KEPEMIMPINAN ADAPTIF SEBAGAI KUNCI SUKSES MEMBANGUN MODEL ORGANIZING HYBRID YANG RELEVAN DAN BERKELANJUTAN - Ainur Rofiq; Istianatul Imamah; Luluk Rosyidatul Umah; Nani Septiana (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The organizing model in the modern education system applies an efficient structural approach, while the salaf education system provides a more intensive depth of values and character development, so adaptive leadership is needed to integrate both in facing current educational challenges. This study aims to interpret the comparison of organizing models in modern and salaf education systems to understand how both models can contribute to the formation of adaptive leadership. The object of the research regarding the comparison of organizing models in modern and salaf education systems is located in the SMA Darussalam. The design in this research uses comparative research with a case study approach. Informants in this research include boarding school administrators, alumni, and quality assurance team. Data collection techniques in this study include observation, interviews, and documentation. Data analysis in this study used the Miles and Huberman data analysis model, which consists of three main steps: data reduction, presentation and conclusion drawing. The results of the research on the comparison of organizing models in modern and salaf education systems produced findings including managerial structures, innovative approach education systems, and teacher welfare program education systems.